Use of surveys to evaluate an integrated oral cholera vaccine campaign in response to a cholera outbreak in Hoima district, Uganda. Issue 12 (10th December 2020) - Bwire, Godfrey; Roskosky, Mellisa; Ballard, Anne; Brooks, W Abdullah; Okello, Alfred; Rafael, Florentina; Ampeire, Immaculate; Orach, Christopher Garimoi; Sack, David A
Abstract : Objectives: To evaluate the quality and coverage of the campaign to distribute oral cholera vaccine (OCV) during a cholera outbreak in Hoima, Uganda to guide future campaigns of cholera vaccine. Design: Survey of communities targeted for vaccination to determine vaccine coverage rates and perceptions of the vaccination campaign, and a separate survey of vaccine staff who carried out the campaign. Setting: Hoima district, Uganda. Participants: Representative clusters of households residing in the communities targeted for vaccination and staff members who conducted the vaccine campaign. Results: Among 209 households (1274 individuals) included in the coverage survey, 1193 (94%; 95% CI 92% to 95%) reported receiving at least one OCV dose and 998 (78%; 95% CI 76% to 81%) reported receiving two doses. Among vaccinated individuals, minor complaints were reported by 71 persons (5.6%). Individuals with 'some' education (primary school or above) were more knowledgeable regarding the required OCV doses compared with non-educated (p=0.03). Factors negatively associated with campaign implementation included community sensitisation time, staff payment and problems with field transport. Although the campaign was carried out quickly, the outbreak was over before the campaign started. Most staff involved in the campaign (93%) were knowledgeable about cholera control; however, 29% did not clearly understand how to detect and manage adverse events following immunisation. Conclusion: The campaign achieved high OCV coverage, but the surveys provided insights for improvement. To achieve high vaccine coverage, more effort is needed for community sensitisation, and additional resources for staff transportation and timely payment for campaign staff is required. Pretest and post-test assessment of staff training can identify and address knowledge and skill gaps.